Lactobacillus johnsonii N6.2 Modulates the Host Immune Responses: A Double-Blind, Randomized Trial in Healthy Adults - Marcial, Guillermo E.; Ford, Amanda L.; Haller, Michael J.; Gezan, Salvador A.; Harrison, Natalie A.; Cai, Dan; Meyer, Julie L.; Perry, Daniel J.; Atkinson, Mark A.; Wasserfall, Clive H.; Garrett, Timothy; Gonzalez, Claudio F.; et al. (Frontiers in Immunology, 2017)
Lactobacillus johnsonii N6.2 mitigates the onset of type 1 diabetes (T1D) in Biobreeding diabetes-prone rats, in part, through changes in kynurenine:tryptophan (K:T) ratios. The goal of this pilot study was to determine the safety, tolerance and general immunological response of L. johnsonii N6.2 in healthy subjects. A double-blind, randomized clinical trial in 42 healthy individuals with no known risk factors for T1D was undertaken to evaluate subject responses to the consumption of L. johnsonii N6.2. Participants received 1 capsule/day containing 108 colony forming units of L. johnsonii N6.2 or placebo for 8 weeks. Comprehensive metabolic profile (CMP), leukocyte subpopulations by complete blood count (CBC) and flow cytometry, serum cytokines and relevant metabolites in the indoleamine-2,3-dioxygenase (IDO) pathway were assessed. L. johnsonii N6.2 survival and intestinal microbiota was analyzed. Daily and weekly questionnaires were assessed for potential effects of probiotic treatment on general wellness. The administration of L. johnsonii N6.2 did not modify the CMP or CBC of participants suggesting general safety. In fact, L. johnsonii N6.2 administration significantly decreased the occurrence of abdominal pain, indigestion and cephalic syndromes. As predicted, increased serum tryptophan levels increased resulting in a decreased K:T ratio was observed in the L. johnsonii N6.2 group. Interestingly, immunophenotyping assays revealed that monocytes and natural killer (NK) cell numbers were increased significantly after wash-out (12 weeks). Moreover, an increase of circulating effector Th1 cells (CD45RO+CD183+CD196-) and cytotoxic CD8+ T cells subset was observed in the L. johnsonii N6.2 group. Consumption of L. johnsonii N6.2 is well tolerated in adult control subjects, demonstrates systemic impacts on innate and adaptive immune populations and results in a decreased K:T ratio. These data provide support for the safety and feasibility of using L. johnsonii N6.2 in prevention trials in subjects at risk for T1D. Trial registration: This trial was registered at clinicaltrials.gov as NCT02349360.